Controversy of Usurpation of Jurisdiction: ICC and Philippines - Villarico, Johndex Emanuel S.; Tobing, Clara Ignatia; Rizkytama, Gunung Ridho; Zakiya, Nathan Luth; Amaliyah, Jihadatun; Nurhasanah, Siti; Alifiah M, Raden Roro Fadhillah; Hariri, Mohammad Rafiq; Pramesti, Salsabila Ayu; Ibrahim, Muhammad (Media Hukum Indonesia (MHI), 2024)
Extra Judicial Killings in the Philippines had caught the attention of various international judicial bodies specially the ICC. The Philippines which a sovereign state was once a signatory of the Rome Statute thus allowing the ICC to have jurisdiction over the country. The ICC conducted a preliminary investigation within the Philippine archipelago for the possible violations of crime against humanity but the Philippines objected to this investigation on grounds that this act of the ICC is an act of usurpation of jurisdiction for the Philippines claimed that they had already withdrawn from the Rome Statute. This paper aims to determine if the act done by the ICC was a true act of usurpation of jurisdiction. This study is a qualitative descriptive analysis and will utilized secondary data as data sources. Upon the analysis of the data gathered, the researcher found out that there is no act of usurpation of jurisdiction done by the ICC. The Philippines may have withdrawn from the Rome Statute, but the investigation conducted by the ICC will only include the extra judicial killings that had occurred from the time that the Philippines was still a signatory of the Rome Statute up to the date prior to their withdrawal.